WHAT IF... WE GOT OUR ATTENTION BACK? - Baird, Vanessa (New Internationalist)
This is because, whatever we like to believe, the brain is not a multitasking device. When you need to pay attention the prefrontal cortex of the brain begins working, helping you to keep focused on a single goal and to carry out that task by co-ordinating messages with other regions of the brain. Clearer beneficiaries are the tech titans - the so called "attention merchants" of Tim Wu's eponymous book - that have penetrated virtually every area and every moment of our lives and turbocharged the multitasking myth.